PENGARUH WORKPLACE SPIRITUALITY DAN OGANIZATIONAL CULTURE TERHADAP EMPLOYEE ENGAGEMENT KARYAWAN GENERASI Y DI PT. KRAMA YUDHA TIGA BERLIAN MOTORS - Supriyanto, S; Riyanto, Setyo (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The dominance of the number of generation Y slowly but surely changing the face of the corporation in Indonesia. The purpose of this research is to investigate the influence of workplace spirituality and organizational culture on employee engagement Generation Y PT. Krama Yudha Tiga Berlian Motors. Sampling method used was sampling incidental to 164 people employees of generation Y from total population of 379 people. Data collection using a questionnaire with Likert scale. Multiple linear regression analysis method used to answer the hypothesis with SPSS ver. 20. The results of this study showed that the variables of workplace spirituality and organizational culture simultaneously have a positive and significant effect on the variable employee engagement. The strongest correlation is between the dimensions meaningfull work found in workplace spirituality variable and the dimensions of vigor found in employee engagement variable. Conducive working atmosphere and the implementation of organizational culture in the company will increase the level of employee engagement. Employee engagement is a very important contributor to the success of a company